Right ventricular stroke work index in pulmonary arterial hypertension and chronic thromboembolic pulmonary hypertension: A retrospective observational study - Györgyi Csósza; Luca Valkó; Elek Dinya; György Losonczy; Veronika Müller; Zsófia Lázár; Kristóf Karlócai (Pulmonary Circulation, 2024)
Abstract The right ventricular stroke work index (RVSWI) reflects the active work of the right ventricle (RV), but its clinical usefulness is not yet fully known in pulmonary arterial hypertension (PAH) and chronic thromboembolic pulmonary hypertension (CTEPH). We aimed to evaluate the correlation of RVSWI to clinical parameters, the presence of comorbidities and response to therapy. We performed a retrospective observational study of 54 patients (PAH: N = 30, CTEPH: N = 24) and control patients (N = 11), and collected clinical data including RVSWI and comorbidities at baseline. We also compared changes in the parameters of the four‐strata mortality risk score at follow‐up (median time of 12 months) after the initiation of therapy between patients with low‐ (<1450 mmHg*mL/m2, N = 18) and high‐RVSWI values (≥1450 mmHg*mL/m2, N = 19). RVSWI at diagnosis was higher in PAH/CTEPH compared to control subjects (1408 ± 391 vs. 704 ± 140 mmHg*mL/m2, p < 0.001, mean ± standard deviation, t‐test), but did not differ between PAH and CTEPH patients (1406 ± 342 vs. 1409 ± 470 mmHg*mL/m2, p = 0.98). Patients without comorbidities had higher RVSWI than those with comorbidities (N = 23: 1522 ± 400 vs. N = 31: 1323 ± 384 mmHg*mL/m2, p = 0.04), which was also found in PAH (p < 0.001), but not in CTEPH (p = 0.37). A greater improvement in the four‐strata mortality risk score (p < 0.05) and a trend for a larger reduction in N‐terminal proB‐type natriuretic peptide concentration (p = 0.06) were observed in the high‐RVSWI subgroup than in the low‐RVSWI patients at follow‐up. In PAH and CTEPH, RVSWI provides additional information on RV function in comorbidities, and it may predict response to specific therapy. Regular monitoring of RVSWI may aid in optimizing therapy selection and timing.